Trade and Development Report 1981 - United Nations Conference on Trade; Development (United Nations, 1981)
This publication identifies the key issues in the global economy and the design of development strategies addressed in the Trade and Development Report over the past three decades, tracing them through its various editions. It shows how ideas, opinions and proposals expressed in the Trade and Development Report, and the analytical approaches used, differed from those of “the mainstream” and their evolution in response to new challenges. This review revisits the concept of interdependence and explains the approach of the reports to macroeconomic and financial policies in both developed and developing countries. It also summarizes development policy failures and successes over the years.